Anatomy of Dissent: Senior U.S. Military Leader Resistance to the Use of Force in the Post-Cold War Era - Burke, Thomas. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Richard Shultz, Jr..; Committee: Robert Pfaltzgraff, Jr., and Abigail Linnington.; Keyword: International relations.